Banana Nutrition Function and Processing Kinetics - Jideani, Afam I. O.; Anyasi, Tonna A. (IntechOpen, 2020)
Banana Nutrition - Function and Processing Kinetics covers the nutritional aspects of the banana plant and fruit. The book contains substantial scientific information written in an easy-to-understand format. The chapters include information on pharmacological aspects of banana; banana bioactives: absorption, utilization, and health benefits; banana pseudo-stem fiber: preparation, characteristics, and applications; banana drying kinetics and technologies; and integrating text mining and network analysis for topic detection from published articles on banana sensory characteristics. All the chapters contain recent advances in science and technology regarding the banana that will appeal to farmers, plant breeders, food industry, investors, and consumers as well as students and researchers. Readers will harness valuable information about the banana in controlling food security and non-communicable nutrition-related human illnesses.